1989
DOI: 10.1016/0035-9203(89)90274-5
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and significance of Cryptosporidium infection in Calcutta

Abstract: During a 2-year study, Cryptosporidium oocysts were detected in 32 (5.6%) of 566 hospitalized paediatric diarrhoea cases and 2 (1.2%) of 167 non-diarrhoeic individuals. Cryptosporidium was the sole pathogen detected in 17 (3.0%) of the 32 positive cases; in the other 15 it occurred in combination with one or more other established enteropathogen(s). The frequency of detection of the parasite was highest in the 0-6 months age group; no sex-specific difference was discernible. The detection rate of the parasite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
6
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 8 publications
5
6
0
Order By: Relevance
“…Our present study from India showed similar observations. The prevalence rates of 4.6% and 1.2% in diarrheic and nondiarrheic cases, respectively, and the peak occurrence of infection in the 0-to 12-month age group are consistent with previous observations of Pal et al (16) and Das et al (6) from the same hospital. This finding is also similar to observations from other developing countries (19) but does not agree with observations described previously by Mathan et al (12), who reported Cryptosporidium infection rates as high as 9.8% in nondiarrheic persons in South India.…”
supporting
confidence: 91%
“…Our present study from India showed similar observations. The prevalence rates of 4.6% and 1.2% in diarrheic and nondiarrheic cases, respectively, and the peak occurrence of infection in the 0-to 12-month age group are consistent with previous observations of Pal et al (16) and Das et al (6) from the same hospital. This finding is also similar to observations from other developing countries (19) but does not agree with observations described previously by Mathan et al (12), who reported Cryptosporidium infection rates as high as 9.8% in nondiarrheic persons in South India.…”
supporting
confidence: 91%
“…The higher prevalence in children and seasonality of infection observed in our study are similar to those in studies reported elsewhere. 1,2,[4][5][6][7]10,19 Thus, the present study demonstrates that Cryptosporidium is an important pathogen associated with diarrhea in children and in the rainy season in Surabaya, Indonesia. Since it was necessary to examine a large number of specimens, we first examined smears concentrated by a floatation technique by phase-contrast microscopy for more rapid viewing.…”
Section: Discussionmentioning
confidence: 92%
“…A number of surveys carried out in recent years have described the worldwide distribution of Cryptosporidium. [1][2][3][4][5][6][7][8][9][10] The prevalence of Cryptosporidium infection is higher among children than among adults and is more common in developing countries than in developed countries. [1][2][3][4][5][6][7][8][9][10] Infection occurs by ingestion of oocysts either through human-to-human or animal-to-human contact, or via contaminated water.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although there was no clear relation with temperature, there was a weak correlation with rainfall (Chai et al 2001). Likewise, a peak incidence was reported in KwaZulu Natal during summer rainfall months (Jarmey-Swan et al 2001) near Pretoria, South Africa, at the end of the rainy season (Fripp et al1991), in Brazil and Costa Rica during the warm rainy months (Mata et al 1984;Mata 1986;Wuhib et al 1994), and in eastern India (Calcutta) during and after the monsoons (Pal and Bhattacharya 1989). To determine the effects of seasonal variability and weather on microbial fecal pollution in an estuary, water samples were collected four times from eight harbor sites in Charleston, South Carolina (Lipp et al 2001).…”
Section: Discussionmentioning
confidence: 91%